Angioplasty With Stent Implantation for Portal Venous Stenosis Caused by Abdominal Tuberculosis: A Case Report and Literature Review - Quan, Xin; Tai, Yang; Wei, Bo; Tong, Huan; Wang, Zhidong; Yang, Yuhang; Wu, Hao (Frontiers in Medicine, 2021)
Abdominal tuberculosis is one of common forms of extra-pulmonary tuberculosis. However, portal vein involvement leading to portal venous stenosis and portal hypertension is a rare complication in abdominal tuberculosis. Because of the non-specific presentations and insensitive response to anti-tuberculosis therapy of the lesions involving portal vein, it continues to be both a diagnostic and treatment challenge. We have reported a 22-year-old woman presented with massive ascites and pleural effusion, which was proved to be TB infection by pleural biopsy. After standard anti-tuberculosis therapy, her systemic symptoms completely resolved while ascites worsened with serum-ascites albumin gradient > 11 g/L. Contrast-enhanced computed tomography and portal venography showed severe main portal vein stenosis from compression by multiple calcified hilar lymph nodes. Finally, the patient was diagnosed with portal venous stenosis due to lymphadenopathy after abdominal tuberculosis infection. Portal venous angioplasty by balloon dilation with stent implantation was performed and continued anti-tuberculosis therapy were administrated after discharge. The ascites resolved promptly with no recurrence occurred during the six-month follow-up. Refractory ascites due to portal venous stenosis is an uncommon vascular complication of abdominal tuberculosis. Portal venous angioplasty with stent placement could be a safe and effective treatment for irreversible vascular lesions after anti-tuberculosis therapy.